RESTAURAÇÃO DE MATAS CILIARES POR PLANTAS TOLERANTES AO ALAGAMENTO: UM ESTUDO DE CASO COM HYMENAEA COURBARIL L. (FABACEAE) - Fernanda Polli Pinheiro (2021)
Riparian forest vegetation is increasingly discussed due to the fundamental role played in maintaining the ecological integrity of water bodies and for their environmental services. Riparian forests are legally defined by the Forest Code as Areas of Permanent Preservation (APP) and, despite being protected by it, they have directly suffered damage caused by human actions, especially in recent decades. Activities such as logging, agricultural use and structural changes resulting from the construction of hydroelectric plants have directly affected these environments. In addition, the APP's vegetation is under constant influence of the flood regime of the rivers, which reflects both on the group of plant species that occur there, and on their ability to survive in an environment with changes in water availability in the soil. In this context, knowledge of the biology of species fully adapted to changes in soil water saturation caused by flood cycles becomes essential for the implementation of environmental restoration projects. This dissertation presents a chapter entitled "Responses to flooding in young plants of Hymenaea courbaril L. (Fabaceae)", in which a controlled experiment was carried out in a greenhouse, and the ecophysiological and morphoanatomical responses of seedlings were evaluated.